Diagnostic Performance of Magnetic Resonance Imaging for Detection of Acute Appendicitis in Pregnant Women; a Systematic Review and Meta-Analysis - Motavaselian, Mohsen; Bayati, Fateme; Amani-Beni, Reza; Khalaji, Amirreza; Haghverdi, Sara; Abdollahi, Zeynab; Sarrafzadeh, Arash; Rafie Manzelat, Amir-masood; Rigi, Amir; Arabzadeh Bahri, Razman; Nakhaee, Zahra; Fadaei, Mahta; et al. (Archives of Academic Emergency Medicine, 2022)
Introduction: The diagnosis of acute appendicitis (AA) in pregnant women is commonly challenging owing to the normal results of laboratory tests, organ displacement, and normal physiological inflammatory alterations. This meta-analysis aimed to investigate the accuracy of magnetic resonance imaging (MRI) in diagnosis of AA in pregnant women. Methods: Two investigators independently performed a comprehensive systematic literature search of electronic databases including MEDLINE, Cochrane Central, EMBASE, Web of Science, Scopus, and Google Scholar to identify studies that reported accuracy of MRI for diagnosis of AA in pregnant women from inception to April 1, 2022. Results: Our systematic search identified a total of 525 published papers. Finally, a total of 26 papers were included in the meta-analysis. The pooled sensitivity and specificity of MRI in diagnosis of AA in pregnant women were 0.92 (95% CI: 0.88–0.95) and 0.98 (95% CI 0.97–0.98), respectively. The pooled positive likelihood ratio and negative likelihood ratio were 29.52 (95% CI: 21.90–39.81) and 0.10 (95% CI: 0.04-0.25), respectively. The area under hierarchical summary receiver operating characteristic (HSROC) curve indicated that the accuracy of MRI for diagnosis of AA in pregnant women is 99%. Conclusion: This meta-analysis showed that MRI has high sensitivity, specificity, and accuracy for diagnosis of AA in pregnant women and can be used as a first-line imaging modality for suspected cases of AA during pregnancy. Furthermore, it should be noted that when the result of ultrasonography is inconclusive, the use of MRI can reduce unnecessary appendectomy in pregnant patients.